1979
DOI: 10.1029/jc084ic11p06969
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and interannual variations in total ozone Revealed by the Nimbus 4 Backscattered Ultraviolet Experiment

Abstract: The first 2 years of backscattered ultraviolet (BUV) ozone data from the Nimbus 4 spacecraft have been processed to a more refined level. The seasonal variations of total ozone for the period April 1970 to April 1972 are described using daily means for 10° latitude zones and a time‐latitude cross section. In addition, the BUV data are compared with analyzed Dobson data and with infrared interferometer spectrometer data also obtained from the Nimbus 4 spacecraft. A harmonic analysis was performed on the daily z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The statement that ozone is known to better than 50% accuracy is not based on model calculations but on observational climatology derived from many years of Dobson measure-ments [see Angell and Korshover, 1978] and 7 years of BUV observations [Hilsenrath et al, 1979].…”
Section: Appendix Asupporting
confidence: 67%
“…The statement that ozone is known to better than 50% accuracy is not based on model calculations but on observational climatology derived from many years of Dobson measure-ments [see Angell and Korshover, 1978] and 7 years of BUV observations [Hilsenrath et al, 1979].…”
Section: Appendix Asupporting
confidence: 67%
“…London et al [1976] halve constructed hemispheric maps of monthly mean total ozone, using Dobson observations from 1957 to 1967. However, Hilsenrath et al [1979] have demonstrated with satellite data that important features were missed in the southern hemisphere because of the scarcity of observing stations. Global ozone trends have been calculated by Angell and Korshover [1978] from ground observations.…”
Section: Introductionmentioning
confidence: 85%
“…However, the parture from sinusiodal behavior of the 2, 1, and 1/2 year semiannual oscillation in the southern hemisphere mid-latiwaves. Shorter period oscillations, which may have a geophys-tudes detected by Hilsenrath et al [1979] in 2 years of data, ical correlation, such as with sotar rotation, can be better iden-persists above the noise in the longer data set. It also appears titled with techniques other than harmonic analysis.…”
Section: Data Basementioning
confidence: 99%
See 2 more Smart Citations